Strategi coping perempuan korban pelecehan seksual ditinjau dari Tipe Kepribadian Eysenck - Jatmika, Devi (Konsorsium Psikologi Ilmiah Nusantara, 2012)
Sexual harassment occurs everywhere, anytime, against especially toward women. This study attempts to find the difference in sexual harassment coping strategies’ based on Eysenck personality type (extrovert-introvert). There are two kinds of coping strategies: a) problem focused coping and b) emotion focused coping. The instrument in this research is a questionnaire that was given to young adulthood women (20-40 years old). Subjects in this research are 192 female. The mean score of problem focused coping dimension is 42.14 (SD=7.64) and the mean score of emotion focused coping dimension is 37.02 (SD=4.19) on women who have introvert personality type. The mean score of problem focused coping dimension is 48.60 (SD=6.69) and the mean score of emotion focused coping dimension is 38.02 (SD=4.02) on women who have extravert personality type. Research hypothesis was denied; c2(1) =0.537, sig/p 0.449> 0.05 thus there is no difference in women coping strategies as victim of sexual harassment.